Dr Analisis Hukum Mengenai Perlindungan Hukum Perdata bagi Pemegang Hak atas Tanah dalam Kasus-Kasus Mafia Tanah di Indonesia: Analisis Hukum Perdata Terhadap Kasus-Kasus Mafia Tanah di Indonesia - Muhammad Kamran; I Dewa Gede Budhy Dharma Asmara (International Journal Of Humanities Education and Social Sciences (IJHESS), 2026)
Land mafia practices in Indonesia are a serious problem that causes harm to land rights holders, both materially and legally. The methods used in land mafia practices include document forgery, unlawful land occupation, abuse of authority, and manipulation of land data, which result in disputes and legal uncertainty regarding land ownership rights. This study aims to analyze the forms of civil legal protection for land rights holders in land mafia cases in Indonesia, as well as the legal remedies available to aggrieved parties. The research method employed is a normative legal analysis using a statutory approach, a conceptual approach, and a case-based approach. Research findings indicate that civil legal protection for land rights holders is regulated by various statutory provisions, particularly in the Basic Agrarian Law and the Civil Code, through mechanisms such as civil lawsuits, certificate revocation, restoration of rights, and claims for damages. However, in practice, this legal protection has not been fully effective due to weaknesses in the land administration system, data overlaps, and the involvement of certain individuals who support land mafia practices. Therefore, it is necessary to strengthen the land administration system, enhance oversight, and enforce the law firmly to provide legal certainty and protection for land rights holders in Indonesia